2020
DOI: 10.7554/elife.53945
|View full text |Cite
|
Sign up to set email alerts
|

Different dendritic domains of the GnRH neuron underlie the pulse and surge modes of GnRH secretion in female mice

Abstract: The gonadotropin-releasing hormone (GnRH) neurons exhibit pulse and surge modes of activity to control fertility. They also exhibit an unusual bipolar morphology comprised of a classical soma-proximal dendritic zone and an elongated secretory process that can operate as both a dendrite and an axon, termed a ‘dendron’. We show using expansion microscopy that the highest density of synaptic inputs to a GnRH neuron exists at its distal dendron. In vivo, selective chemogenetic inhibition of the GnRH neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 48 publications
0
59
1
Order By: Relevance
“…The proximal GnRH neuron dendrite was the focus of this study, as GABAergic remodeling is restricted to this region [ 14 , 16 ]. However, we cannot rule out changes at the more distal GnRH neuron dendron, the region known to be critical in driving pulsatile LH secretion [ 59 ]. In any case, the present finding stands in contrast to the plasticity that has been observed in the GABA ARN -to-GnRH neuron circuit, despite NPY ARN neurons composing a large proportion of this circuit [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proximal GnRH neuron dendrite was the focus of this study, as GABAergic remodeling is restricted to this region [ 14 , 16 ]. However, we cannot rule out changes at the more distal GnRH neuron dendron, the region known to be critical in driving pulsatile LH secretion [ 59 ]. In any case, the present finding stands in contrast to the plasticity that has been observed in the GABA ARN -to-GnRH neuron circuit, despite NPY ARN neurons composing a large proportion of this circuit [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The functional difficulties imposed by this topography appear to be solved, in part, by GnRH neurons focusing their blended dendritic/axonal projections on the median eminence where they can be regulated in a concerted manner by the KNDy pulse generator (Herbison 2018). While it is clear that classic synaptic inputs exist on the GnRH neuron dendron (Moore, Prescott et al 2018, Wang, Guo et al 2020, we note that this is not the case for the KNDy neuron innervation. Although many close appositions were identified with regular confocal analysis, no evidence was found with ExM for these to be synaptic inputs between KNDy fibers and GnRH neuron dendrons.…”
Section: Kisspeptin In Kndy Neurons Is Essential For Episodic Activatmentioning
confidence: 87%
“…Expansion microscopy (ExM) uses isotropic swelling of the tissue specimen to provide ~70 nm spatial resolution that can reliably image synapses in the brain (Wassie, Zhao et al 2019). We have previously demonstrated using ExM that a "sideplane" overlap of >0.23 μm (0.95 μm post-expansion) or face-plane (z stack) overlap >0.42 μm (1.75 μm post-expansion) between a synaptophysin-immunoreactive bouton and the GFP of a GnRH neuron represents a bona fide synapse (Wang, Guo et al 2020). The presence of kisspeptin synapses on distal dendrons was examined by assessing synaptophysin-containing kisspeptin boutons opposed to GFP-expressing dendrons.…”
Section: Kndy Neurons Signal Through Volume Transmission To the Gnrh mentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that proximal segments of GnRH dendrites have a pivotal role in the physiology of the cells. They express active ion conductances, generate action potentials and contribute-via synaptic inputs-to the surge release of the hormone (Iremonger and Herbison 2015;Wang et al 2020;Norberg et al 2013).…”
Section: Quantification Of the Neuronal Glp-1 Input To Hypophysiotropmentioning
confidence: 99%